Development of encapsulation and release of model proteins in hydroxyapatite nanoparticles - Law, Yi Ping. (2009)
Hydroxyapatite (HA) nanoparticles have been studied as carriers for the delivery of therapeutic agents. The two important considerations of the carriers are the encapsulation abilities and the release profiles. This report presents a model study of encapsulating and release of model proteins from HA nanoparticles. The double inverse microemulsion (DIME) method of synthesis was used to produce HA nanoparticles and encapsulate model proteins within. The effects of synthesis by this method on the size, encapsulation capabilities and release profiles were studied, using the co-precipitation method as a control. The DIME was shown to have encapsulation capabilities but the release results did not show a controlled sustained release.